2019
DOI: 10.1002/jcb.28972
|View full text |Cite
|
Sign up to set email alerts
|

The role of P2Y6 receptors in the maintenance of neuropathic pain and its improvement of oxidative stress in rats

Abstract: Aim To explore the role of P2Y6 receptors in the maintenance of neuropathic pain and progression of oxidative stress, we investigated the efficacy of the selective P2Y6 receptors antagonist MRS2578 on the antiallodynic effects and improvement of pathological neuropathic pain‐induced oxidative stress, thereby finding a potential therapeutic target in neurological disease. Materials and Methods The mechanical allodynia in the ipsilateral spinal dorsal horn (SDH) of rats was observed in rats after chronic constri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Changes in low-molecular-weight molecule expression have been reported as possibly being involved in different types of pathological pain. For instance, a decline in antioxidant molecules such as glutathione (307 Da) induces mechanical allodynia and thermal hyperalgesia after CCI, the l -lactate (89 Da) overload resulting from aberrant spinal astrocyte neuron lactate shuttle, has been associated with neuropathic pain maintenance, and levels of tetrahydrobiopterin (BH4; 241 Da) are dramatically increased in sensory neurons after peripheral nerve damage increasing pain hypersensitivity. , …”
Section: Resultsmentioning
confidence: 99%
“…Changes in low-molecular-weight molecule expression have been reported as possibly being involved in different types of pathological pain. For instance, a decline in antioxidant molecules such as glutathione (307 Da) induces mechanical allodynia and thermal hyperalgesia after CCI, the l -lactate (89 Da) overload resulting from aberrant spinal astrocyte neuron lactate shuttle, has been associated with neuropathic pain maintenance, and levels of tetrahydrobiopterin (BH4; 241 Da) are dramatically increased in sensory neurons after peripheral nerve damage increasing pain hypersensitivity. , …”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence suggests that nuclear factor-erythroid 2-related factor/antioxidant responsive element (NRF2/ARE) and PPAR-γ/PPAR-γ response element (PRE) pathways regulate redox signaling and the underlying mechanisms to control oxidative stress, inflammation and overcome mitochondrial impairment [37,38]. Indeed, synthetic and natural agents that abrogate nitroso-oxidative stress and free radical scavengers were well reported to inhibit neuropathic pain [34,[38][39][40][41]. It is possible that pioglitazone activated antioxidant mechanisms might be contributed to attenuate the development of neuropathic pain and sustained long-term effects and such protective effects were abolished by PAPR-γ antagonist BADGE in ipsilateral paws of mononeuropathic rats.…”
Section: Discussionmentioning
confidence: 99%
“…There has been no prior study on the thiol/disulfide balance reported, but the relationship of PKU with many original oxidative stress parameters has been evaluated in the literatüre [9][10][11][12][13][14]. We examined how it affects the thiol/disulfide balance in PKU in our study.…”
Section: Introductionmentioning
confidence: 99%